Nanosilver wire-graphene chemical self-assembly material and preparation method and application thereof

The metal-carbon cluster structure is constructed through nano-silver wire-graphene chemical self-assembly materials, which solves the problem that existing electromagnetic shielding materials cannot meet the high electromagnetic shielding needs in high-frequency environments, and achieves high-efficiency electromagnetic shielding effect during high-speed and high-frequency operation of 6G communication and electronic devices.

CN118994517BActive Publication Date: 2025-02-28UNIV OF ELECTRONICS SCI & TECH OF CHINA ZHONGSHAN INST
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411247685.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-02-28
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

The existing electromagnetic shielding materials fail to make full use of eddy current loss to absorb electromagnetic waves, resulting in the inability to meet the high-electromagnetic shielding requirements during 6G communication and high-speed and high-frequency operation of electronic devices.

Method used

Using nano-silver wire-graphene chemical self-assembly materials, the metal-carbon cluster structure is constructed by depositing or embedded nano-silver wires on the graphene surface to realize the reflection and absorption of electromagnetic waves.

Benefits of technology

It significantly improves electromagnetic shielding performance and can achieve efficient electromagnetic wave reflection and absorption in the 8.2-12.4GHz band, meeting the high-frequency operation needs of 6G communication and electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005031301430000131
    Figure BDA0005031301430000131
  • Figure HDA0005031301460000011
    Figure HDA0005031301460000011
  • Figure HDA0005031301460000021
    Figure HDA0005031301460000021
Patent Text Reader

Abstract

The invention belongs to the technical field of electromagnetic shielding materials, and specifically discloses a nano silver wire-graphene chemical self-assembly material and a preparation method and application thereof. The nano silver wire with surface group activation is used as a reflection unit, and the graphene with surface group activation is used as an absorption unit. Through the reaction with an active bridging carrier (a binary end group reactive small molecule), spatial self-assembly between the nano silver wire and the graphene is achieved to prepare spatial cluster particles with high electromagnetic shielding energy efficiency. The preparation method has the characteristics of simplicity, good repeatability, easy control of process conditions, etc. The prepared nano silver wire-graphene chemical self-assembly cluster particles have excellent reflection and absorption electromagnetic wave energy efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electromagnetic shielding materials, in particular to a nano silver wire-graphene chemical self-assembly material and a preparation method and application thereof. Background Art

[0002] The advancement of 6G and electronic information technology has brought high-speed data transmission and device interconnection, but it has also led to the complexity of the electromagnetic environment and the intensification of EMI problems. To address these challenges, advanced electromagnetic shielding materials and design technologies have been introduced to improve the anti-interference ability and stability of equipment and promote continuous technological innovation. At the same time, packaging materials for electronic information products are also facing higher requirements, including electromagnetic shielding, heat dissipation, temperature resistance, environmental protection, sustainability and cost-effectiveness. At present, electromagnetic shielding technology does not fully utilize eddy current loss to absorb electromagnetic waves, which may cause secondary pollution. Future research should improve material molding, solve nanofiller agglomeration, develop low-cost environmentally friendly materials, and construct new composite materials that can reflect and absorb electromagnetic waves to promote breakthroughs in electromagnetic shielding technology.

[0003] Chinese patent application number CN201810167725.8 discloses a method for preparing a high-screen-efficiency flexible window film using nano silver wires, comprising: (1) preparing nano silver wires; (2) preparing an assembled film using the Langmuir-Buget technique; (3) modifying the assembled film; (4) immersing the modified assembled film in a modified graphene solution, adding a condensation agent, reacting, washing, and drying to obtain a high-screen-efficiency flexible window film; although the high-screen-efficiency flexible window film prepared by this method is assembled from nano silver wires and graphene and has a certain electromagnetic shielding effect, it cannot meet the high electromagnetic shielding requirements required for high-speed and high-frequency operation performance of 6G communications and electronic devices. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a nano silver wire-graphene chemical self-assembly material and a preparation method and application thereof.

[0005] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0006] One of the purposes of the present invention is to provide a method for preparing a nano silver wire-graphene chemical self-assembly material, comprising the following steps:

[0007] S1. Take the aminated silver nanowires and aminated graphene at a mass ratio of 0.5:1 to 2.5:1, and disperse the aminated silver nanowires in N,N-dimethylformamide (DMF) to obtain an N,N-dimethylformamide dispersion of the aminated silver nanowires with a concentration of 1 mg / ml; dissolve the N,N-dimethylformamide dispersion of the aminated silver nanowires and the aminated graphene in N,N-dimethylformamide, and ultrasonically disperse for 20 minutes to obtain a mixed dispersion A;

[0008] S2, stirring the mixed dispersion A and heating it to 80°C, adding a bridging assembly agent 10 times the mass of the amino graphene, keeping stirring and gradually heating it to 90°C;

[0009] S3. When the temperature reaches 90°C, 0.05% of the mass of the bridging assembly agent dibutyltin dilaurate (DBTDL) is dissolved in an acetone solvent to obtain an acetone solution of dibutyltin dilaurate with a concentration of 0.01 g / ml; the acetone solution of dibutyltin dilaurate is quickly added to the mixed dispersion A, and the reaction is continued by stirring for 2 to 8 hours to obtain a mixed dispersion B;

[0010] S4, the obtained mixed dispersion B is slightly shaken and then ultrasonically dispersed for 30s to 1min., and a precipitate is obtained by centrifugation. The precipitate is washed with N,N-dimethylformamide, ethanol, and acetone for 2 to 3 times in sequence to obtain an acetone dispersion C of nanosilver wire-graphene self-assembled cluster particles;

[0011] S5, concentrating the acetone dispersion C of the nano silver wire-graphene self-assembled cluster particles and fixing the volume to 0.8 mg / ml, thereby obtaining the acetone dispersion D of the nano silver wire-graphene self-assembled cluster particles;

[0012] S6. Using a polytetrafluoroethylene plate as a substrate, spin-coat the nanosilver wire-graphene self-assembled cluster particle acetone dispersion D into a film at room temperature, and then place it in an oven at 50-80°C for 72 hours. Peel the film off the polytetrafluoroethylene plate to obtain a nanosilver wire-graphene chemical self-assembled material.

[0013] Furthermore, the bridging assembly agent is isophorone diisocyanate (IPDI).

[0014] Furthermore, in step S1, the preparation method of the amination nano silver wire is:

[0015] S11, adding silver nanowires and cysteamine hydrochloride in a mass ratio of 20:1 into 50 ml of N,N-dimethylformamide solvent, and slowly stirring to obtain a precursor mixed dispersion;

[0016] S12, in a dark environment and at room temperature, stirring the precursor dispersion at a constant temperature for 0.5 to 4 hours, and centrifuging to obtain precipitated particles;

[0017] S13. The precipitated particles are washed alternately with deionized water, anhydrous ethanol and N,N-dimethylformamide twice each to completely remove cysteamine hydrochloride to obtain amino-modified nanosilver wires.

[0018] Preferably, the purity of the amino graphene is greater than 98%, the number of layers is less than 10, and the sheet diameter is 0.5 to 10 μm;

[0019] Preferably, the centrifugal separation in step S4 is carried out on a refrigerated centrifuge at a centrifugal speed of 5000 r / min.

[0020] The second purpose of the present invention is to provide a nano silver wire-graphene chemical self-assembly material prepared by the above method.

[0021] The third purpose of the present invention is to provide an application of a nano silver wire-graphene chemical self-assembly material in the preparation of an electromagnetic shielding film.

[0022] Compared with the prior art, the present invention uses -NH2-activated nano silver wires as electromagnetic wave reflection units, -NH2-activated graphene as wave absorption units, and binary reactive monomers as bridge segments. Through the chemical reaction of the active end groups with -NH2, the nano silver wires are deposited on the graphene surface or embedded between graphene layers, realizing the chemical assembly of the spatial structure between the nano silver wires and the graphene, constructing a metal-carbon cluster structure that has both the energy efficiency of reflecting and absorbing electromagnetic waves, and preparing cluster particle functional devices with both reflection and absorption electromagnetic wave functional characteristics. The preparation method has the characteristics of simplicity, good repeatability, and easy control of process conditions. The prepared self-assembled cluster particles can be directly film-formed without the need for multi-layer film-forming structure design. The film-forming process is simple, and the film material has excellent energy efficiency of reflecting and absorbing electromagnetic waves. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a reaction flow chart of the method for preparing the nano silver wire-graphene chemical self-assembly structure.

[0024] Figure 2 The scanning electron microscope (SEM) scanning characterization results of the silver nanowire-graphene chemical self-assembled cluster particles and silver nanowires, aminated silver nanowires, and aminated graphene prepared in Example 1 of the present invention are as follows: (a) is the morphology of the silver nanowire, with a smooth and clean surface; (b) is the morphology of the aminated silver nanowire, on the surface of which small particles are clearly observed to be attached, which is cysteamine; (c) is the morphology of the aminated graphene, and the layered stacking structure of the graphene particles can be clearly observed; (d) is the morphology of the self-assembled cluster particles.

[0025] Figure 3The SEM-OXFORD Ultim Extreme EDS spectrometer test characterization results of the silver nanowire-graphene chemical self-assembled cluster particles prepared in Example 1 of the present invention are: (a) is the EDS test position image; (b) is the C element distribution; (c) is the Ag element distribution; (d) is the N element distribution.

[0026] Figure 4 These are the X-ray photoelectron spectroscopy (XPS) test characterization results of the silver nanowire-graphene chemical self-assembled cluster particles and the amino silver nanowires, amino graphene, and silver nanowires prepared in Example 1 of the present invention.

[0027] Figure 5 This is the Raman spectrum (Raman) test characterization result of the nano silver wire-graphene chemical self-assembled cluster particles prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.

[0029] Unless otherwise specified, the raw materials and reagents used in the following examples were commercially available.

[0030] Example 1

[0031] 1) Preparation of aminated silver nanowires and N,N-dimethylformamide dispersion of aminated silver nanowires

[0032] Weigh 0.015 g of cysteamine hydrochloride and 0.3 g of nanosilver wires into 50 ml of DMF, slowly stir to obtain a precursor mixed dispersion; transfer to a 150 ml three-necked flask and place in an ultrasonic oscillator; react with ultrasonic oscillation at room temperature for 45 min under light-proof conditions; centrifuge the reaction solution to obtain amino nanosilver wires, and wash them alternately with deionized water, anhydrous ethanol and DMF twice each to completely remove the modifier cysteamine hydrochloride, and make the volume to 1 mg / ml with DMF to obtain N,N-dimethylformamide dispersion of amino nanosilver wires.

[0033] 2) Preparation of silver nanowire-graphene self-assembled cluster particle dispersion

[0034] 0.02 g of amino graphene (purchased from Chengdu Jiacai Technology Co., Ltd.: purity > 98%, number of layers < 10, sheet diameter 0.5-10 μm) and 80 ml of DMF were placed in a 150 ml clean three-necked flask and dispersed in an ultrasonic oscillator for 20 min. The three-necked flask was moved to a heating mantle with a magnetic stirring function, and 20 ml of 1mg / ml amination nanosilver wire DMF dispersion (ultrasonic dispersion for 20min.); set the magnetic stirrer speed to 1000rph / min., continue mixing and stirring for 10min, so that the nanosilver wire is fully dispersed in the system, to obtain suspension A; continue stirring the suspension A, and heat it to 80℃, add 0.2g of bonding assembly agent isophorone diisocyanate (IPDI), and gradually heat it to 90℃; when the temperature reaches 90℃, quickly add 1ml of dibutyltin dilaurate acetone solution (take 0.0001g dibutyltin dilaurate (DBTDL) and dissolve it in acetone solution The method comprises the following steps: preparing a suspension B, ultrasonically dispersing the suspension B in an ultrasonic oscillator for 10 min., and then centrifuging the suspension B at a speed of 5000 rph / min. to obtain a precipitate, and washing and separating the precipitate 3-5 times with DMF, ethanol and acetone as solvents in turn to fully remove free IPDI that does not participate in the reaction; and finally dispersing the precipitate with acetone to obtain an acetone dispersion of nano silver wire-graphene self-assembled cluster particles at a fixed volume of 0.8 mg / ml, i.e., nano silver wire-graphene self-assembled cluster particle dispersion D.

[0035] The morphologies of the silver nanowire-graphene self-assembled cluster particles, silver nanowires, amino-treated silver nanowires, and amino-treated graphene in dispersion D were tested using a Hitachi SU5000 scanning electron microscope (SEM). Figure 2 The SEM-OXFORD Ultim Extreme EDS spectrometer test results of the silver nanowire-graphene self-assembled cluster particles are shown in Figure 3 As shown. Figure 2 In the figure, (a) is the morphology of silver nanowires, with a smooth and clean surface; (b) is the morphology of amino-treated silver nanowires, with small particles of cysteamine clearly observed on the surface; (c) is the morphology of amino-treated graphene, with the layered stacking structure of graphene particles clearly observed; (d) is the morphology of self-assembled cluster particles. Figure 3 In the figure, (a) is the EDS test position image; (b) is the C element distribution; (c) is the Ag element distribution; (d) is the N element distribution. Figure 3 It can be clearly seen that Ag, C, and N elements exist and are distributed in a position, and the N content is relatively high. The reason for this result is that the self-assembly system still contains a large amount of free bridge bonding agent IPDI. Figure 2 and Figure 3 The results show that the silver nanowires are attached to or penetrate the surface or interlayer of graphene, that is, the silver nanowires achieve spatial self-assembly between graphene.

[0036] Furthermore, the above-mentioned silver nanowire-graphene self-assembled cluster particles, silver nanowires, amino-treated silver nanowires, and amino-treated graphene were tested using an X-ray photoelectron spectrometer (XPS) and a Raman spectrometer, respectively. The results are as follows: Figure 4 and Figure 5 shown.

[0037] exist Figure 4 In the experiment, the contents of C, Ag and N in amino-treated silver nanowires, amino-treated graphene and self-assembled cluster particles were compared. All four particles contained C and N elements. The C and N elements in the silver nanowires mainly came from the morphology control agent polyvinyl pyrrolidone (PVP); the C and N elements in the amino-treated silver nanowires and amino-treated graphene mainly came from the -NH2 activation modifier on the surface of the nanoparticles, that is, the surface of the nanoparticles contained -NH2 groups; the C and N elements in the self-assembled cluster particles mainly came from the -NH2 activation modifier and the bridging agent isophorone diisocyanate (IPDI), and the ratio of the N content to the silver content in the self-assembled cluster particles (W N / W Ag =0.29) is significantly higher than the corresponding ratio in amino-treated silver nanowires (0.14), which indicates that the self-assembled cluster particles contain the N element in the bonding assembling agent IPDI.

[0038] exist Figure 5 Middle, located at 2923cm -1 The absorption peak at 1710 cm represents the characteristic absorption peak of -CH2-. -1 The absorption peak at 1585 cm represents the absorption peak of -(C=O)-. -1 The absorption peak at 1360 cm represents the characteristic absorption peak of -NH-. -1The absorption peak at represents the characteristic absorption peak of -CN-. The characteristic absorption peaks representing -NH- and -CN- appeared in the Raman spectra of the aminated nanosilver wire and the aminated graphene, indicating that the surfaces of both particles contain -NH2; in the structure of the self-assembled cluster particles, not only the characteristic absorption peaks representing -NH- and -CN- appeared, but also the characteristic absorption peaks representing -CH2- and -(C=O)-; in the Raman spectrum of the nanosilver wire particles, the absorption peaks of -CH2- and -CN- also appeared near the same position, but the position of the characteristic absorption peaks of the aminated nanosilver wire was shifted, which is related to the presence of the morphology control agent PVP and the salting effect of the tertiary amine structure in the structure. The results of Raman spectroscopy further illustrate that the nanosilver wire and graphene achieve spatial structural self-assembly through the reaction between -NH2 and the -NCO group in IPDI to form a urea bridge segment.

[0039] 3) Preparation of nanosilver wire-graphene chemical self-assembly materials

[0040] Place a polytetrafluoroethylene plate on a vacuum coater, turn on the vacuum system to firmly adsorb the plate; ultrasonically disperse a 0.8 mg / ml nanosilver wire-graphene self-assembled particle dispersion for 5 minutes; use a graduated tube to draw 2.5 ml of the solution and slowly drip it on the surface of the polytetrafluoroethylene plate; adjust the coater speed to 50 rph / min, rotate at a constant speed for 2 minutes, reduce the speed to zero, and let it stand for 1 hour to ensure that the solvent evaporates cleanly to obtain a self-assembled particle film; continue to repeat the coating process for 9 times according to the above process to obtain a multilayer self-assembled particle film; place the coated film in an oven at 50-80°C and bake it at a constant temperature for 72 hours, peel off the film from the plate to obtain a nanosilver wire-graphene chemical self-assembled material with a thickness of about 20 μm, recorded as sample 1.

[0041] Example 2

[0042] 1) Preparation of aminated silver nanowires and N,N-dimethylformamide dispersion of aminated silver nanowires

[0043] The preparation method is the same as Example 1.

[0044] 2) Preparation of silver nanowire-graphene self-assembled cluster particle dispersion

[0045] 0.02 g of amino graphene (purchased from Chengdu Jiacai Technology Co., Ltd.: purity > 98%, number of layers < 10, sheet diameter 0.5-10 μm) and 90 ml of DMF were placed in a 100 ml clean three-necked flask and dispersed in an ultrasonic oscillator for 20 min. The three-necked flask was moved to a heating mantle with a magnetic stirring function, and 10 ml of 1mg / ml amination nanosilver wire DMF dispersion (ultrasonic dispersion for 20min.); set the speed of the magnetic stirrer to 1000rph / min., and continue mixing and stirring for 10min. to fully disperse the nanosilver wire in the system to obtain suspension A; continue stirring the suspension A, and heat it to 80℃, add 0.2g of bridging assembly agent isophorone diisocyanate (IPDI), and gradually heat it to 90℃; when the temperature reaches 90℃, quickly add 1ml of acetone solution of dibutyltin dilaurate (take 0.0001g dibutyltin dilaurate (DBTDL) and dissolve it in acetone solution) The suspension B was obtained by ultrasonically dispersing the suspension B in an ultrasonic oscillator for 10 min., and then centrifuging the suspension at a speed of 5000 rph / min. to obtain a precipitate, and washing and separating the precipitate 3-5 times with DMF, ethanol and acetone as solvents in turn to fully remove free IPDI that did not participate in the reaction; finally, the suspension was dispersed with acetone to obtain an acetone dispersion of nano silver wire-graphene self-assembled cluster particles at a fixed volume of 0.8 mg / ml, i.e., nano silver wire-graphene self-assembled cluster particle dispersion D.

[0046] 3) Preparation of nanosilver wire-graphene chemical self-assembly materials

[0047] The film was prepared by referring to Example 1 to obtain Sample 2.

[0048] Example 3

[0049] 1) Preparation of aminated silver nanowires and N,N-dimethylformamide dispersion of aminated silver nanowires

[0050] The preparation method is the same as that of Example 1;

[0051] 2) Preparation of silver nanowire-graphene self-assembled cluster particle dispersion

[0052] 0.02 g of amino graphene (purchased from Chengdu Jiacai Technology Co., Ltd.: purity > 98%, number of layers < 10, sheet diameter 0.5-10 μm) and 70 ml of DMF were placed in a 100 ml clean three-necked flask and dispersed in an ultrasonic oscillator for 20 min. The three-necked flask was moved to a heating mantle with a magnetic stirring function, and 30 ml of 1 mg / ml of amino silver nanowire DMF dispersion (ultrasonic dispersion for 20 min.); set the magnetic stirrer speed to 1000 rph / min., continue mixing and stirring for 10 min to fully disperse the silver nanowires in the system to obtain suspension A; continue stirring the suspension A, and heat it to 80°C, add 0.2 g of bridging assembly agent isophorone diisocyanate (IPDI), and gradually heat it to 90°C; when the temperature reaches 90°C, quickly add 1 ml of acetone solution of dibutyltin dilaurate (take 0.0001 g of dibutyltin dilaurate (DBTDL) and dissolve it in acetone solution The method comprises the following steps: preparing a suspension B, ultrasonically dispersing the suspension B in an ultrasonic oscillator for 10 min., and then centrifuging the suspension B at a speed of 5000 rph / min. to obtain a precipitate, and washing and separating the precipitate 3-5 times with DMF, ethanol and acetone as solvents in turn to fully remove free IPDI that does not participate in the reaction; and finally dispersing the precipitate with acetone to obtain an acetone dispersion of nano silver wire-graphene self-assembled cluster particles at a fixed volume of 0.8 mg / ml, i.e., nano silver wire-graphene self-assembled cluster particle dispersion D.

[0053] 3) Preparation of nanosilver wire-graphene chemical self-assembly materials

[0054] The film was prepared by referring to Example 1 to obtain Sample 3.

[0055] Example 4

[0056] 1) Preparation of aminated silver nanowires and N,N-dimethylformamide dispersion of aminated silver nanowires

[0057] The preparation method is the same as that of Example 1.

[0058] 2) Preparation of silver nanowire-graphene self-assembled cluster particle dispersion

[0059] 0.02 g of amino graphene (purchased from Chengdu Jiacai Technology Co., Ltd.: purity > 98%, number of layers < 10, sheet diameter 0.5-10 μm) and 60 ml of DMF were placed in a 100 ml clean three-necked flask and dispersed in an ultrasonic oscillator for 20 min. The three-necked flask was moved to a heating mantle with a magnetic stirring function, and 40 ml of 1mg / ml amination silver nanowire DMF solution (ultrasonic dispersion for 20min.); set the magnetic stirrer speed to 1000rph / min., continue mixing and stirring for 10min, so that the silver nanowires are fully dispersed in the system, and obtain suspension A; continue stirring suspension A, and heat it to 80℃, add 0.2g bridging assembly agent isophorone diisocyanate (IPDI), and gradually heat it to 90℃; when the temperature reaches 90℃, quickly add 1ml acetone solution of dibutyltin dilaurate (take 0.0001g dibutyltin dilaurate (DBTDL) and dissolve it in acetone solution The method comprises the following steps: preparing a suspension B, ultrasonically dispersing the suspension B in an ultrasonic oscillator for 10 min., and then centrifuging the suspension B at a speed of 5000 rph / min. to obtain a precipitate, and washing and separating the precipitate 3-5 times with DMF, ethanol and acetone as solvents in turn to fully remove free IPDI that does not participate in the reaction; and finally dispersing the precipitate with acetone to obtain an acetone dispersion of nano silver wire-graphene self-assembled cluster particles at a fixed volume of 0.8 mg / ml, i.e., nano silver wire-graphene self-assembled cluster particle dispersion D.

[0060] 3) Preparation of nanosilver wire-graphene chemical self-assembly materials

[0061] The film was prepared by referring to Example 1 to obtain Sample 4.

[0062] Example 5

[0063] 1) Preparation of aminated silver nanowires and N,N-dimethylformamide dispersion of aminated silver nanowires

[0064] The preparation method is the same as that of Example 1;

[0065] 2) Preparation of silver nanowire-graphene self-assembled cluster particle dispersion

[0066] 0.02 g of amino graphene (purchased from Chengdu Jiacai Technology Co., Ltd.: purity > 98%, number of layers < 10, sheet diameter 0.5-10 μm) and 50 ml of DMF were placed in a 100 ml clean three-necked flask and dispersed in an ultrasonic oscillator for 20 min. The three-necked flask was moved to a heating mantle with a magnetic stirring function, and 50 ml of 1mg / ml amination silver nanowire DMF solution (ultrasonic dispersion for 20min.); set the magnetic stirrer speed to 1000rph / min., continue mixing and stirring for 10min, so that the silver nanowires are fully dispersed in the system, and obtain suspension A; continue stirring suspension A, and heat it to 80℃, add 0.2g bridging assembly agent isophorone diisocyanate (IPDI), and gradually heat it to 90℃; when the temperature reaches 90℃, quickly add 1ml acetone solution of dibutyltin dilaurate (take 0.0001g dibutyltin dilaurate (DBTDL) and dissolve it in acetone solution The method comprises the following steps: preparing a suspension B, ultrasonically dispersing the suspension B in an ultrasonic oscillator for 10 min., and then centrifuging the suspension B at a speed of 5000 rph / min. to obtain a precipitate, and washing and separating the precipitate 3-5 times with DMF, ethanol and acetone as solvents in turn to fully remove free IPDI that does not participate in the reaction; and finally dispersing the precipitate with acetone to obtain an acetone dispersion of nano silver wire-graphene self-assembled cluster particles at a fixed volume of 0.8 mg / ml, i.e., nano silver wire-graphene self-assembled cluster particle dispersion D.

[0067] 3) Preparation of nanosilver wire-graphene chemical self-assembly materials

[0068] The film was prepared by referring to Example 1 to obtain Sample 5.

[0069] Comparative Example 1: Preparation of Nanosilver Wire Film

[0070] 1) Preparation of silver nanowire dispersion

[0071] 50 ml of DMF and 50 ml of 1 mg / ml amination nanosilver wire DMF dispersion were placed in a 150 ml clean three-necked flask and ultrasonically dispersed for 20 min. The three-necked flask was moved to a heating mantle with a magnetic stirring function, and the speed of the magnetic stirrer was set to 1000 rph / min. The mixing and stirring were continued for 10 min to fully disperse the nanosilver wire in the system to obtain a suspension A. The suspension A was continuously stirred and heated to 80°C, 0.2 g of a bridging assembly agent isophorone diisocyanate (IPDI) was added, and the temperature was gradually raised to 90°C; when the temperature reached 90°C, 1 ml of an acetone solution of dibutyltin dilaurate ( 0.0001 g of dibutyltin dilaurate (DBTDL) was dissolved in an acetone solution to obtain an acetone solution of dibutyltin dilaurate with a concentration of 0.01 g / ml), and the reaction was stirred for 2 hours to obtain a suspension B; the suspension B was ultrasonically dispersed in an ultrasonic oscillator for 10 min., and then centrifuged at a speed of 5000 rph / min. to obtain a precipitate, and DMF, ethanol, and acetone were used as solvents for washing and separation 3-5 times in sequence to remove free IPDI; finally, the suspension was dispersed with acetone to obtain a nano silver wire particle acetone dispersion with a fixed volume of 0.8 mg / ml, i.e., nano silver wire particle dispersion E.

[0072] 3) Preparation of silver nanowire film

[0073] Place a polytetrafluoroethylene plate on a vacuum coater, turn on the vacuum system to firmly adsorb the plate; ultrasonically disperse the nanosilver wire particle dispersion E with a concentration of 0.8 mg / ml for 5 min; use a graduated tube to draw 2.5 ml of the solution and slowly drip it on the surface of the polytetrafluoroethylene plate; adjust the coater speed to 50 rph / min, rotate at a constant speed for 2 min, reduce the speed to zero, and let it stand for 1 h to ensure that the solvent evaporates cleanly to obtain a self-assembled particle film; continue to repeat the coating process for 9 times according to the above process to obtain a multilayer self-assembled particle film; place the coated film in an oven at 50-80°C and bake it at a constant temperature for 72 h, peel off the film from the plate to obtain a nanosilver wire film with a thickness of about 20 μm, recorded as sample 6.

[0074] Comparative Example 2: Preparation of graphene film

[0075] 1) Preparation of graphene dispersion

[0076] 0.02 g of amino graphene (purchased from Chengdu Jiacai Technology Co., Ltd.: purity> 98%, number of layers<10, sheet diameter of 0.5-10 μm) was placed in a 150 ml clean three-necked flask, DMF was added, and ultrasonic dispersion was performed for 20 min.; the three-necked flask was moved to a heating mantle with a magnetic stirring function, the speed of the magnetic stirrer was set to 1000 rph / min., and mixing and stirring were continued for 10 min to fully disperse the amino graphene to obtain suspension A; the suspension A was continuously stirred and heated to 80° C., 0.2 g of bridging assembly agent isophorone diisocyanate (IPDI) was added, and the temperature was gradually raised to 90° C. When the temperature reached 90° C., 1 ml of acetone solution of dibutyltin dilaurate (0.0001 g of dibutyltin dilaurate (DBTDL) was dissolved in acetone solution to obtain an acetone solution of dibutyltin dilaurate with a concentration of 0.01 g / ml) was quickly added, and the reaction was stirred for 2 hours to obtain suspension B; the suspension B was ultrasonically dispersed in an ultrasonic oscillator for 10 min., and then centrifuged at a speed of 5000 rph / min. to obtain a precipitate, and DMF, ethanol, and acetone were used as solvents for washing and separation for 3-5 times in sequence to remove free IPDI; finally, the suspension was dispersed with acetone to obtain a graphene acetone dispersion with a fixed volume of 0.8 mg / ml, i.e., graphene dispersion F.

[0077] 2) Preparation of graphene film

[0078] Place a polytetrafluoroethylene plate on a vacuum coater, turn on the vacuum system to firmly adsorb the plate; ultrasonically disperse graphene dispersion F with a concentration of 0.8 mg / ml for 5 minutes; use a graduated tube to draw 2.5 ml of the solution and slowly drip it on the surface of the polytetrafluoroethylene plate; adjust the coater speed to 50 rph / min, rotate at a constant speed for 2 minutes, reduce the speed to zero, and let it stand for 1 hour to ensure that the solvent evaporates completely to obtain a self-assembled particle film; continue to repeat the coating process for 9 times according to the above process to obtain a multilayer self-assembled particle film; place the coated film in an oven at 50-80°C and bake it at a constant temperature for 72 hours, peel off the film from the plate to obtain a graphene film with a thickness of about 20 μm, recorded as sample 7.

[0079] Samples 1 to 7 were prepared and tested for electromagnetic shielding efficiency in the 8.2-12.4 GHz band using a waveguide method using a waveguide test system consisting of an Agilent N5247A vector network analyzer, a waveguide tube, and a coaxial test battery according to ASTM ES7-83 and ASTM D4935-99. The sample size was 40 mm × 40 mm × 20 μm and the test temperature was room temperature. The test results are shown in Table 1.

[0080] The prepared samples 1 to 7 were respectively taken and the resistivity was tested using a ST-2258C four-probe resistivity tester (ST-2258A), the sample size was 40 mm × 40 mm × 20 μm, and the test temperature was room temperature. The test results are shown in Table 1.

[0081] Table 1 Average electromagnetic shielding efficiency and resistivity of films of different embodiments and comparative examples

[0082]

[0083] *It is the average electromagnetic shielding efficiency of the film in the 8.2-12.4 GHz band.

[0084] In Table 1, Comparative Example 1 is a nano silver wire film, and its electromagnetic shielding efficiency SE R 33.22dB, significantly larger than SE A (9.35dB), that is, the nano silver wire film is an electromagnetic shielding material that mainly reflects electromagnetic waves; Comparative Example 2 is a graphene film, and its electromagnetic shielding efficiency SE R (11.24dB) and SE A (25.48dB) gap is reduced, that is, the graphene film is an electromagnetic shielding material that "mainly absorbs waves and also has the ability to reflect" electromagnetic waves. Examples 1 to 5 are nanosilver wire-graphene self-assembled cluster particle films (the mass ratio of nanosilver wire to graphene is different). Compared with nanosilver wire films and graphene films, the electromagnetic shielding efficiency (SE T ) is significantly higher than the former. With the increase of the proportion of nano silver wires, the SE of the film T The value keeps increasing. When the mass ratio of nano silver wire to graphene is 2.5:1, SE T Reached 67.25dB. T The reason for the increase in the value is that the silver nanowires are embedded in the inner layer of the graphene particles or stacked between the graphene particles, so that the electromagnetic waves reflected by the silver nanowires form a scattered eddy current loop between the graphene layers or particles, which is continuously absorbed in the form of energy loss, showing as SE A As the proportion of nanosilver wires increases, more nanosilver wires are embedded in the inner layer of graphene particles or stacked between graphene particles, and the eddy current loss effect of electromagnetic waves becomes more obvious, resulting in SE A The value keeps increasing; at the same time, the increase in the content of nano silver wires will also increase the degree of electromagnetic wave reflection, resulting in SE R Keep getting bigger.

[0085] In summary, the nano silver wire-graphene chemical self-assembled cluster structure prepared by the present invention can significantly improve the electromagnetic shielding performance of the material, and the self-assembled structure material has excellent reflection and absorption efficiency of electromagnetic waves, and therefore, can be used to prepare electromagnetic shielding films.

[0086] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a nano silver wire-graphene chemical self-assembly material, characterized in that: The following steps are involved: S1. Take the aminated silver nanowires and aminated graphene in a mass ratio of 0.5:1 to 2.5:1, and disperse the aminated silver nanowires in N,N-dimethylformamide to obtain an N,N-dimethylformamide dispersion of the aminated silver nanowires with a concentration of 1 mg / ml; dissolve the N,N-dimethylformamide dispersion of the aminated silver nanowires and the aminated graphene in N,N-dimethylformamide, and perform ultrasonic dispersion for 20 minutes to obtain a mixed dispersion A; S2, stirring the mixed dispersion A and heating it to 80° C., adding a bridging assembly agent of 10 times the mass of the amino graphene, keeping stirring and gradually heating to 90° C.; the bridging assembly agent is isophorone diisocyanate; S3. When the temperature reaches 90°C, 0.05% of the mass of the bridging assembly agent dibutyltin dilaurate is dissolved in an acetone solvent to obtain an acetone solution of dibutyltin dilaurate with a concentration of 0.01 g / ml; the acetone solution of dibutyltin dilaurate is quickly added to the mixed dispersion A, and the reaction is continued by stirring for 2 to 8 hours to obtain a mixed dispersion B; S4, the obtained mixed dispersion B is slightly shaken and then ultrasonically dispersed for 30s to 1min, and centrifuged to obtain a precipitate, and the precipitate is washed with N,N-dimethylformamide, ethanol, and acetone for 2 to 3 times in sequence to obtain an acetone dispersion C of nanosilver wire-graphene self-assembled cluster particles; S5, concentrating the acetone dispersion C of the nano silver wire-graphene self-assembled cluster particles and fixing the volume to 0.8 mg / ml, thereby obtaining the acetone dispersion D of the nano silver wire-graphene self-assembled cluster particles; S6. Using a polytetrafluoroethylene plate as a substrate, spin-coat the nanosilver wire-graphene self-assembled cluster particle acetone dispersion D into a film at room temperature, then place it in an oven at 50-80°C for 72 hours, peel off the film from the polytetrafluoroethylene plate, and obtain the nanosilver wire-graphene chemical self-assembled material.

2. The method for preparing the nano silver wire-graphene chemical self-assembly material according to claim 1, characterized in that: In step S1, the preparation method of the amination nano silver wire is: S11, adding silver nanowires and cysteamine hydrochloride in a mass ratio of 20:1 into 50 ml of N,N-dimethylformamide solvent, and slowly stirring to obtain a precursor mixed dispersion; S12, in a dark environment and at room temperature, stirring the precursor dispersion at a constant temperature for 0.5 to 4 hours, and centrifuging to obtain precipitated particles; S13. The precipitated particles were washed alternately with deionized water, anhydrous ethanol and N,N-dimethylformamide twice each to completely remove cysteamine hydrochloride, thereby obtaining amino-modified nanosilver wires.

3. The method for preparing the silver nanowire-graphene chemical self-assembly material according to claim 1, characterized in that: The purity of the amino graphene is greater than 98%, the number of layers is less than 10, and the sheet diameter is 0.5 to 10 μm.

4. The method for preparing the silver nanowire-graphene chemical self-assembly material according to claim 1, characterized in that: The centrifugal separation in step S4 is performed on a refrigerated centrifuge at a centrifugal speed of 5000 r / min.

5. A nano silver wire-graphene chemical self-assembly material prepared by the method according to any one of claims 1 to 4.

6. Use of the nano silver wire-graphene chemical self-assembly material as claimed in claim 5 in the preparation of electromagnetic shielding film.

Citation Information

Patent Citations

  • Method for preparing high-screen-efficiency flexible window film by using nano silver wire

    CN108376573A

  • Preparation method of graphene-nano silver dispersion liquid

    CN106903324A

  • A nanocomposite, a filtration membrane comprising the nanocomposite, and methods to form the nanocomposite and the filtration membrane

    WO2012177223A1